A DESCRIPTIVE ANALYSIS OF THE USE OF ICE BREAKING TECHNIQUE IN LEARNING ENGLISH AT SMP NEGERI 2 JAYAPURA - Halisa nia (FKIP Universitas Cenderawasih, 2023)
Icebreakers are commonly used by trainers or instructors to maintain group dynamic. In fact, there is a growing interest for language teachers to use icebreakers in the classes. The current study focuses on the role of the ice breaking technique in increasing students’ interest in learning English. 70 students from SMP Negeri 2 Abepura were involved in this study. This study was conducted within a qualitative descriptive design using observation, interview, and questionnaire to collect the data. The results of the observation and interview showed that the use of icebreakers in the classes showed potentials in motivating the students to learn English in accordance with Sapp’s principles of icebreakers: simplicity, relevance, non-threat, open-endedness, and energizing. Besides, the result of the questionnaire showed that the students had a positive perception on the ice breaking technique applied by the teacher during the English classes. The majority of the students (> 60%) agreed that the ice breaking activities were motivating in terms of the principles. Overall, the ice breaking techniques was likely to increase the students' interest in learning English in terms of the principles.Keywords: icebreaking technique, students’ interest, learning English Icebreakers biasanya digunakan para pelatih atau instruktur untuk mempertahankan dinamika kelompok. Pada kenyataannya, ada paningkatan minat terhadap penggunaan icebreakers dalam pembelajaran bahasa. Penelitian ini berfokus pada peran teknik ice breaking dalam meningkatkan minat siswa dalam belajar bahasa Inggris. Penelitian ini melibatkan 70 siswa kelas dari SMP Negeri 2 Abepura. Penelitian ini dilaksanakan dengan metode deskriptif kualitatif dengan menggunakan observasi, wawancara, dan kuesioner untuk mengumpulkan data. Hasil observasi dan wawancara menunjukkan bahwa teknik ice breaking memiliki potensi dalam memotivasi siswa untuk belajar bahasa Inggris berdasarkan prinsip icebreakers menurut Sapp yaitu sederhana, relevant, tidak membahayakan, terbuka, dan memberi semangat. Selain itu, hasil dari kuesioner menunjukkan bahwa para siswa memiliki persepsi positif tentang teknik ice breaking yang diterapkan oleh guru selama kelas bahasa Inggris. Mayoritas siswa (>60%) setuju bahwa setuju bahwa kegiatan icebreakers memotivasi mereka berdasarkan kelima prinsip yang ada. Secara keseluruhan, teknik icebreakeryang digunakan berpotensi meningkatkan minat siswa dalam belajar bahasa Inggris dalam kaitannya dengan prinsip-prinsip yang ada. Kata kunci: Teknik ice breaking, minat siswa, belajar bahasa Inggris